PMM.51 An Accurate Semi-Automated Oscillometric Blood Pressure (BP) Device for Use in Pregnancy in a Low- and Middle-Income Country Population: the Microlife 3AS1–2. (9th June 2014) - Nathan, HL; De Greeff, A; Hezelgrave, NL; Chappell, LC; Shennan, AH
Abstract : Objectives: To assess the Microlife 3AS1–2, a semi-automated oscillometric BP device, compared to mercury sphygmomanometry for use in pregnancy and pre-eclampsia in a low resource setting, according to the requirements of the British Hypertension Society (BHS) Protocol 1 and the International Organisation of Standardisation (ISO). 2 Methods: Prospective observational study, using validation methods recommended by the BHS. 45 pregnant subjects were recruited, including 15 with pre-eclampsia, 10 in their second trimester, 10 from their third trimester and 10 with an arm circumference >35 cm, from Kimberley Hospital, South Africa. All participants were provided with written consent. any subject with cardiac arrhythmia or unclear Korotkoff sounds was excluded. Results: The Microlife 3AS1–2 device achieved an overall B/A grade, with an A/A grade in pregnancy excluding pre-eclampsia (n = 30) and passed all the BHS protocol requirements. The device achieved the ISO standard for mean difference and standard deviation (≤ 5 ± 8 mmHg) in pregnancy (including pre-eclampsia). Conclusion: The Microlife 3AS1–2 device can be recommended for use in pregnancy, including pre-eclampsia, according to BHS and ISO protocols. As well as demonstrating accuracy in a low-resource pregnant population, it also fulfils all of the requirements stipulated by the World Health Organisation for an automated device suitable for use in a low-resource setting. This makes it the ideal device for use in antenatal clinics and primary health-care facilities in low- and middle-income countries. References: International Standard (ISO). Non-invasive sphygmomanometers. Part 2: Clinical investigation of automated measurement type. 2013 O'Brien E, et al . The British Hypertension Society protocol for the evaluation of blood pressure measuring devices. J Hypertens. 1993;11(Suppl 2):S43–S62